Character Education in Early Childhood Based on Family - Uswatun Hasanah; Much Deiniatur (Department of Early childhood Education, 2019)
Family is a place of learning that is full of true love and affection. Good characters embodied in the family are very fundamental human characteristics. Children’s capability to function as responsible citizens must be nurtured early on. Family is the smallest social unit that has an important role in the development of children's character, which lies in character education model given by the parents to their children. Character education within a family has not been conceptualized in a way that leads to a variety of educational praxis according to the understanding of each parent. The purpose of the study is to describe what values can be internalized to a family since early childhood. The research method used is literature study (library research), which is a research conducted by the researchers by collecting a number of books, magazines, leaflets pertaining to problems and research objectives. The findings show that children's character education should start from within the family, because family is the smallest unit of society and it will depend on parents to teach children from early age. Children’s character building within the family is not an easy practice because it requires systemic handling. There are interrelationships of other components, such as schools and community environments, which is necessary in its implementation. Character education in early childhood should start from the family through the eight family functions including (1) Education Function, (2) Protection Function, (3) Affection function, (4) Socialization function, (5) Reproduction Function, (6) Religious Functions, (7) Economic Functions, and (8) Recreation Functions.